The Travel Diaries of Albert Einstein : South America, 1925 - Einstein, Albert, 1879-1955 (Book collections on Project MUSE., 2022)
"A marvelously annotated and illustrated edition of Einstein's South America travel diary. In the spring of 1925, Albert Einstein embarked on an extensive lecture tour of Argentina before continuing on to Uruguay and Brazil. In his travel diary, the preeminent scientist and humanitarian icon recorded his immediate impressions and broader reflections on the people he encountered and the locations he visited. Some of the most confounding passages reveal his uncensored views on his host nations. This edition makes available the complete journal Einstein kept on his three-month journey. In these remarkable pages, Einstein enthuses about the stunning vistas of lush vegetation in Rio de Janeiro. His flight in the skies over Buenos Aires thrills him, and he enjoys the cozy atmosphere of Montevideo. He expresses genuine admiration for the Uruguayans, harsh condescension toward the Argentinians, and ambivalent affection for the Brazilians. The illustrious visitor seeks calm refuge on the long ocean voyages, far from the madding crowds of Europe, but the grueling lecture schedule and the adoration of the local masses exhaust him.This edition features stunning facsimiles of the diary's pages accompanied by an English translation, an extensive historical introduction, numerous illustrations, and editorial annotations. Supplementary materials include letters, postcards, statements, and speeches as well as a chronology, a bibliography, and an index"--